Women and conflict in the Middle East : Palestinian refugees and the response to violence - Holt, Maria (New York : I.B. Tauris, 2014)
Women in conflict zones face a wide range of violence: from physical and psychological trauma to political, economic and social disadvantage. And the sources of the violence are varied also: from the'public' violence of the enemy to the more'private' violence of the family. Here, Maria Holt, using research gathered in the Palestinian refugee camps of Lebanon and in the West Bank in 2007, looks at the forms of violence suffered by women in the context of the wider conflict around them. Drawing on first-hand accounts of women who have either participated in, been victims of or bystanders to violence, this book highlights the complex situation of these refugees, and explores how many of them become involved in resistance activities. It thus makes essential reading for students of the Israel-Palestine conflict as well as those interested in the gender dimension of conflict.
Includes bibliographical references (pages [261]-276), notes and index.
Keywords: Women, Palestinian Arab -- West Bank -- Social conditions; Women, Palestinian Arab -- Lebanon -- Social conditions; Refugees, Palestinian Arab -- West Bank -- Social conditions; Refugees, Palestinian Arab -- Lebanon -- Social conditions; Women, Palestinian Arab -- Political activity -- West Bank; Women, Palestinian Arab -- Political activity -- Lebanon; Women, Palestinian Arab -- Violence against -- West Bank; Women, Palestinian Arab -- Violence against -- Lebanon